2013
DOI: 10.1364/ol.38.003322
|View full text |Cite
|
Sign up to set email alerts
|

Arbitrary-detuning asynchronous optical sampling pump-probe spectroscopy of bacterial reaction centers

Abstract: A recently reported variant of asynchronous optical sampling compatible with arbitrary unstabilized laser repetition rates is applied to pump-probe spectroscopy. This makes possible the use of a 5.1 MHz chirped pulse oscillator as the pump laser, thus extending the available time window to almost 200 ns with a time resolution as good as about 320 fs. The method is illustrated with the measurement in a single experiment of the complete charge transfer dynamics of the reaction center from Rhodobacter sphaeroides. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Optoelectronic ADASOPS can thus be readily combined with multiscale control and rapid scanning of time delays up to millisecond timescales [25]. Finally, the higher TDC acquisition rate will be of great interest when a long-cavity oscillator is used as the pump laser, in which case the low coincidence rate was so far the main factor limiting the time resolution [14].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Optoelectronic ADASOPS can thus be readily combined with multiscale control and rapid scanning of time delays up to millisecond timescales [25]. Finally, the higher TDC acquisition rate will be of great interest when a long-cavity oscillator is used as the pump laser, in which case the low coincidence rate was so far the main factor limiting the time resolution [14].…”
Section: Discussionmentioning
confidence: 99%
“…The basic principle of ADASOPS relies on the determination and regular update of the law of delay evolution between pump and probe pulses. This law can subsequently be used to accumulate measured data in appropriate time bins [14] or to decide which pulse to selectively amplify [25]. If we number each probe pulse with an integer i, the law of delay evolution can be approximated with the following expression of the time delay ∆t i elapsed since the previous pump pulse,…”
Section: Principle Of Optoelectronic Adasopsmentioning
confidence: 99%
See 2 more Smart Citations
“…The conventional ASOPS approach is a stroboscopic method based on two femtosecond oscillators with nearly identical repetition frequencies or near multiples. However, over the past decade, the Joffre group demonstrated an arbitrary-detuning ASOPS (AD-ASOPS) that utilizes two oscillators with arbitrarily different repetition frequencies. Their AD-ASOPS does not require dedicated oscillators specially set up for conventional ASOPS. An early version of AD-ASOPS was based on an interferometric detection of coincidences between pulses to measure the pump–probe delay time a posteriori . , More recently, they showed that a couple of photodetectors and a time-to-digital converter combined with a frequency divider and a pulse selector could be used to enable a high-rate electronic measurement of the delay between pump and probe pulses .…”
Section: Conventional Nonlinear Spectroscopy With a Single Mode-locke...mentioning
confidence: 99%